2013
DOI: 10.1097/inf.0b013e318287f02a
|View full text |Cite
|
Sign up to set email alerts
|

Infectious Complications of Intrathecal Baclofen Pump Devices in a Pediatric Population

Abstract: Infectious complications were relatively uncommon; however, when present, frequently led to the explantation of the ITB pump device.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
29
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 23 publications
3
29
1
Order By: Relevance
“…3 Few studies have investigated postoperative complication and infection rates of ITBP in the pediatric population, and findings are limited. 4,10,15 Increased mechanical complications between 1997 and 2006 were reported in 1 study. 15 Surgical-site infections (SSI) accounted for 31% of all hospital-acquired infection among hospitalized patients, according to a report by Magill et al, 8 and the overall rate of SSI reported by the National Healthcare Safety Network was 1.9%.…”
mentioning
confidence: 99%
“…3 Few studies have investigated postoperative complication and infection rates of ITBP in the pediatric population, and findings are limited. 4,10,15 Increased mechanical complications between 1997 and 2006 were reported in 1 study. 15 Surgical-site infections (SSI) accounted for 31% of all hospital-acquired infection among hospitalized patients, according to a report by Magill et al, 8 and the overall rate of SSI reported by the National Healthcare Safety Network was 1.9%.…”
mentioning
confidence: 99%
“…8,9 Although treatment failure or infection recurrence have been reported in device-related infections, particularly when the device is not removed, we found no reports in the literature of baclofen pump device infections that recurred after device removal. 2,5,10,11 We report a case of a patient with recurrent A xylosoxidans meningitis associated with an intrathecal baclofen pump device.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] Commonly reported pathogens include Staphylococcus aureus (both methicillin susceptible and resistant) and coagulase-negative Staphylococcus, but Enterococcus species and gram-negative pathogens have been reported as well. [2][3]5 Depending on the extent of the infection, therapy may include systemic antibiotics and/or device removal. 6 Achromobacter xylosoxidans is an aerobic gram-negative bacillus found in the environment, particularly in water.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations